2020
DOI: 10.3390/su12187647
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Urban Green at Reduction of Particulate Matters in Sihwa Industrial Complex, Korea

Abstract: The utilization of urban green areas has increased, but it is unclear whether urban green areas can decrease the concentration of particulate matter at an industrial complex city in Korea. We measured the extent of particulate matter (PM) reduction at a buffer green area in the Sihwa Industrial Complex. PM was measured at the industrial complex, the urban green area, and a nearby residential area from April to October 2019. PM reduction rates were highest at the urban green area in August and October, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…In most areas, even if locals wish to access green areas, it is difficult to do so without proper environmental management and green infrastructure [13]. As fundamental environmental elements that can provide ecosystem services, management of green areas is necessary to enhance the quality of life, for environmental conservation, and to reduce disaster risk in urban and rural areas [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In most areas, even if locals wish to access green areas, it is difficult to do so without proper environmental management and green infrastructure [13]. As fundamental environmental elements that can provide ecosystem services, management of green areas is necessary to enhance the quality of life, for environmental conservation, and to reduce disaster risk in urban and rural areas [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to represent the monthly PM concentration because PM measurement was carried out during just 1 day. However, we identified days with monthly weather characteristics in advance, and previous studies also showed monthly PM concentrations as a result of measuring PM for a short time [24,29]. So, we can speculate that our measuring data can show the feature of monthly PM.…”
Section: Pm Measurement At Human Breathing Heightmentioning
confidence: 84%
“…However, we considered not only the effect of GB but also the distance effect on PM reduction according to the distance from air pollutant emitters. PM 10 and PM 2.5 , which have a long atmospheric lifetime, decreased [60]; thus, we can speculate that the influence of the GB on PM reduction was greater than that of distance [24].…”
Section: The Effect Of Pm Reduction Of the Gb Zone At Human Breathing Heightmentioning
confidence: 85%
See 2 more Smart Citations